Using Analytical Approach to Estimate Wave Transmission Coefficient in Floating Structures - Alamailes, Abubaker; Turker, Umut (Asce-Amer Soc Civil Engineers, 2019)
This paper presents a simplified analytical approach, based on power transmission theory, to estimate the transmission coefficient of a floating box structure with finite width. In evaluating the transmitted wave power, this approach considers both the incident wave power and the heave oscillation of the floating structure. Additional power due to the acceleration of the floating body and the hydrodynamic mass increases the transmitted wave power behind the floating structure and consequently increases the transmission coefficient. The proposed theoretical approach was validated using laboratory-scale experimental data obtained from the literature for floating breakwaters and wave energy converters. The results of the proposed approach were in good to excellent agreement with those of experimental studies. In addition, the reliability of the present model was assessed by comparing its results with those of other theoretical approximations. The effects of sea depth, relative draft, and incident wave height on the magnitude of the transmission coefficient distinguish the proposed model from others in the existing literature.
Keywords: Floating structure; Hydrodynamic mass; Incident power; Transmission coefficient; Transmitted power; Wave transmission